Durable response of chemotherapy for cancer of unknown primary with unfavorable subset developed in retroperitoneal space. Issue 4 (27th May 2021) - Matsukawa, Atsuki; Kato, Taigo; Kondo, Fuki; Kawasaki, Keisuke; Kawashima, Atsunari; Kiuchi, Hiroshi; Imamura, Ryoichi; Uemura, Motohide; Fukuhara, Shinichiro; Morii, Eiichi; Nonomura, Norio
Abstract : Introduction: Carcinoma of unknown primary site is a heterogeneous group of cancer that is defined by the presence of metastatic disease with no identified primary tumor at initial presentation. Carcinoma of unknown primary site patients with unfavorable subsets particularly show poor prognosis with a median survival of 6–9 months with the treatment of empirical pactitaxel and carboplatin therapy (TC therapy). Recently, several studies have attempted to increase the response rate on the basis of prediction of the primary site by immunohistochemical tests or molecular profiling assays. Case presentation: We report the case of a 77‐year‐old woman who presented with a mass on the left side of the abdominal aorta. Careful clinical and laboratory examinations could not identify the site of primary cancer. Pathologic examination of biopsied tissue revealed the tumor as undifferentiated carcinoma, which reached the diagnosis of carcinoma of unknown primary site with unfavorable subsets. She received empirical TC therapy and had prolonged survival of 26 months. After reviewing the pathological findings carefully, we noticed that Gross Cystic Disease Fluid Protein‐15 showed positive in the tumor, leading to the suspicion of breast cancer as the primary site. The specific therapy for breast cancer is similar to the empirical TC therapy in carcinoma of unknown primary site, which may contribute durable response in this patient. Conclusion: Site‐specific therapy based on careful immunohistochemical tests may improve the efficacy for carcinoma of unknown primary site patients with unfavorable prognosis subset.